2020
DOI: 10.3390/s20205831
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-Year Analysis of NO2 Concentration Measurements at Belisario Station (Quito, Ecuador) Using Statistical Inference Techniques

Abstract: In this paper, a robust analysis of nitrogen dioxide (NO2) concentration measurements taken at Belisario station (Quito, Ecuador) was performed. The data used for the analysis constitute a set of measurements taken from 1 January 2008 to 31 December 2019. Furthermore, the analysis was carried out in a robust way, defining variables that represent years, months, days and hours, and classifying these variables based on estimates of the central tendency and dispersion of the data. The estimators used here were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
(93 reference statements)
2
7
0
Order By: Relevance
“…The contribution of the present research is that it has been shown that this periodic behavior can be represented by using 95% confidence intervals, both robust and nonrobust ones. Furthermore, the range of possible values of these signals has been categorized with robust statistical precision, which is in agreement with what was discovered in [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…The contribution of the present research is that it has been shown that this periodic behavior can be represented by using 95% confidence intervals, both robust and nonrobust ones. Furthermore, the range of possible values of these signals has been categorized with robust statistical precision, which is in agreement with what was discovered in [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 87%
“…The existence of maximum and minimum values in the concentration of air pollutants has also been observed in other research [ 50 , 51 , 86 ]. The reality is that anthropogenic emissions have a great influence on the levels of air pollutants in urban cities.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations